Observation of the effect of the use of two different dressings on the catheter infection during continuous renal replacement therapy - ZHANG Meng; GUO Wei (Linchuang shenzangbing zazhi)
Objective To investigate the influence of two different dressings on catheter infection in process of continuous renal replacement therapy( CRRT) for patients in ICU. Methods A prospective study was undertaken. All of 80 patients treated with CRRT who used temporary central venous catheter were randomly divided into transparent dressing group and double gauze group,40 patients were in each groups. in the case of the setting of the tube and the catheter and all of the operations were strictly adhered to the principles of the sterile operating principle,it was measured by the age,the blood,the albumin,the urea nitrogen,the renal function,the placement of the time and the space of the area,and the time and the location of the patient,and the criteria for the diagnostic criteria,and the clinical practice,to determine the diagnostic criteria for the infection and to terminate the diagnostic criteria of the tube,and to do the study. Results The rates of temporary central venous catheter infection in the double gauze group( 10%,22. 5%) were higher than those in transparent dressing group( 0,5%) after 2-5 weeks and 6-9 weeks,t here was significant difference between the two groups( χ~2 = 4. 037,5. 518; P = 0. 044,0. 035); The total rate of temporary central venous catheter infection in the double gauze group( 32. 5%) was also significantly higher than thatin transparent dressing group( 5. 0%)( χ~2 = 6. 136,P = 0. 013). Compared with the traditional gauze,sticking in sealing better,safer,can effectively isolates external pathogens,reduce the incidence of catheter infections,but in a long time of catheter withhold treatment,two groups the incidence of catheter infections increased,this and recent research results of the catheter infection rate and the catheter withhold time there is a close contact. Conclusions The using of transparent dressing in process of CRRT could reduce the rate of temporary central venous catheter infection compared with the gauze for patients in ICU. At the same time,it can reduce the cost of patients to stay in ICU,and it is worth promoting and applying in clinic.